Glory - Zwick, Edward; Broderick, Matthew, 1962-; Washington, Denzel, 1954-; Elwes, Cary, 1962-; Freeman, Morgan; Kennedy, Jihmi; Braugher, Andre; Finn, John; Leitch, Donovan; Cullum, John David; Gunton, Bob.; De Young, Cliff (Burbank, CA : RCA/Columbia Pictrues Home video, 1989)
Exceptional story of America's first unit of black soldiers during the Civil War and the young, inexperienced Northerner who's given the job of training and leading them.
Produced by Freddie Fields; directed by Edward Zwick; screenplay by Kevin jarre; music by James Horner.
Starring Matthew Broderick, Denzel Washington, Cary Elwes, Morgan Freeman, Jihmi Kennedy, Andre Braugher, John finn, Donovan Leitch, John David Cullum, bob Gunton and Cliff DeYoung.
MPAA Rating: R.
VHS
Keywords: Shaw, Robert Gould, -- 1837-1863.; United States -- History -- Civil War, 1861-1865 -- Regimental histories; United States -- History -- Civil War, 1861-1865 -- African Americans; United States -- History -- Civil War, 1861-1865 -- Campaigns; Feature films; War films and programs